Perancangan Sistem Informasi Pengawasan dan Pengadaan Persediaan Barang Berbasis Web pada PT Yudha Daya Elektrik Mandiri - Baleri, Primus Desideratus; Saifudin, Aries (Program Studi Teknik Informatika Universitas Pamulang, 2022)
PT. Yudha Daya Elektrik Mandiri is a company engaged in the mechanical and electrical sector that is specifically related to power generation, either in the form of products, namely: Panels, Bank Capacitors and in the form of automatic systems. In the administrative process of procurement of goods, employees have difficulty in searching for goods in the warehouse because there is no system that can know incoming goods and outgoing goods. The inventory of goods is also still done manually using paper, then after that it will be inputted into Ms-Word or Ms-Excel, based on this method, which must be done repeatedly will cause errors and even lose items and will take a long time. At the time of making reports, there are still frequent mismatches of goods in the warehouse with records of incoming goods and outgoing goods and that can cause losses. In this study, in terms of collecting data using the method of observation, interviews, and literature studies, for the system development method using the waterfall method. The results of this research are the monitoring and procurement system of goods, there is an item data menu that can control incoming and outgoing goods, making it easier to control the goods in the warehouse and a menu feature that can be easily used by admins in making reports automatically because they are connected. directly with the sale of goods so that the report will match the data in the warehouse and develop the system to the android version.